PENINGKATAN EKONOMI KELUARGA MELALUI PROGRAM PEMBINAAN DAN PELATIHAN WIRAUSAHA KERAJINAN LIMBAH ORGANIK BAGI KELOMPOK PKK NAGARI SUNUR TIMUR - Alkadri, Hanif; Santoso, Yulianto; Widiawati, Widiawati; Achyar, Nofriyanti; Susanti, Lusi; Gistituati, Nurhizrah (Jurnal Abdi Masyarakat, 2023)
A maintained environment with good waste management will make the environment healthier. Utilization of waste can be an economical item to be a current trend that is good to follow and support. Kenagari Sunur is an area that will receive organic waste in the form of corn husks. However, this waste has not been optimally processed and utilized. Only a small portion has been used to support the people's economy, but it is still traditional in nature and does not show significant development and progress both in terms of product and economic value. Therefore, this training activity aims to 1) provide training to PKK Nagari Sunur Timur group women to take advantage of local superior potential, 2) provide guidance to existing business actors to develop and increase creativity. This service was carried out at the Sereh Wangi Korong PKK Secretariat, Kabun Sunur, Nan Sabaris District, with 20 training participants. The charity activities carried out were very beneficial for PKK Nagari Sunur mothers. Community service activities were also attended by participants with enthusiasm and enthusiasm and almost all participants understood and were fluent in practicing the manufacture of products that had been trained.